CLONING AND EXPRESSION OF CHAETOMIUM THERMOPHILUM XYLANASE 11-A GENE IN PROKARYOTE - Wajid, S.; Latif, F.; Afzal, S.; Mukhtar, Z.; Ghaffar, A.; Mansoor, S.; Rajoka, I. (The Nucleus, 2020)
The xylanase gene was cloned into pET32a(+) and expressed in E. coli BL21 under T7 promotor alongwith fusion protein. The SDS-PAGE and western blot analysis showed a protein of 42 kDa. The best expression of xylanase enzyme was found by using xylose as carbon source and lactose as an inducer. The maximum activity of xylanase expressed in E. coli was 6.02 U/mL in the presence of 2 % xylose in DS medium. The activity of recombinant xylanase was observed on 1 % xylan LB agar plates, showed halos of xylan clearance when lactose was used as an inducer.